A software tool: Type-2 fuzzy logic toolbox - Ozek, Muzeyyen Bulut; Akpolat, Zuhtu Hakan (John Wiley & Sons Inc, 2008)
The concept of type-2 fuzzy set was initially proposed as an extension of classical (type-1) fuzzy sets. Type-2 fuzzy sets are very useful in circumstances where it is difficult to determine an exact membership function for a fuzzy set; hence they are very effective for dealing with uncertainties. However, type-2 fuzzy sets are more difficult to use and understand than type-1 fuzzy sets. Even in the face of these difficulties, type-2 fuzzy logic has found applications in many fields. In this article, a new Type-2 Fuzzy Logic Toolbox written in MATLAB programming language is introduced. The main aim is to help the user to understand and implement type-2 fuzzy logic systems easily. Type-2 Fuzzy Logic Controller Block is also prepared for use in SIMULINK. Since general type-2 fuzzy logic systems are very complicated, they are not preferred in applications. Thus, only interval type-2 fuzzy logic systems are considered in the proposed Type-2 Fuzzy Logic Toolbox. Since MATLAB Fuzzy Logic Toolbox users are familiar with its windows, all the menus of the developed software are prepared in the same format of the MATLAB Fuzzy Logic Toolbox. (c) 2008 Wiley Periodicals, Inc.
Keywords: type-2 fuzzy logic; type-2 fuzzy sets; interval sets; type-2 fuzzy logic toolbox